Beryllium-isotope signatures in ice sheet proximal marine sediments - Matthew Richard Jeromson; Toshiyuki Fujioka; David Fink; Krista Simon; Alexandra L. Post; Marcello Blaxell; José Tonatiuh Sánchez-Palacios; T. Gabriel Enge; Carly Beggs; Duanne A. White (Chemical Geology, 2025)

Circumpolar Deep Water upwelling is a primary source of 10Be in Antarctic continental shelf sediments - Matthew R. Jeromson; Toshiyuki Fujioka; David Fink; Krista Simon; James Smith; Claus-Dieter Hillenbrand; Gerhard Kuhn; Alexandra L. Post; Jose Tonatiuh Sánchez-Palacios; Marcello Blaxell; T. Gabriel Enge; Duanne A. White (Global and Planetary Change, 2024)

Responses of Southern Ocean Seafloor Habitats and Communities to Global and Local Drivers of Change - Madeleine J. Brasier; David Barnes; Narissa Bax; Angelika Brandt; Anne B. Christianson; Andrew J. Constable; Rachel Downey; Blanca Figuerola; Huw Griffiths; Julian Gutt; Susanne Lockhart; Simon A. Morley; et al. (Frontiers in Marine Science, 2021)
Knowledge of life on the Southern Ocean seafloor has substantially grown since the beginning of this century with increasing ship-based surveys and regular monitoring sites, new technologies and greatly enhanced data sharing. However, seafloor habitats and their communities exhibit high spatial variability and heterogeneity that challenges the way in which we assess the state of the Southern Ocean benthos on larger scales. The Antarctic shelf is rich in diversity compared with deeper water areas, important for storing carbon (“blue carbon”) and provides habitat for commercial fish species. In this paper, we focus on the seafloor habitats of the Antarctic shelf, which are vulnerable to drivers of change including increasing ocean temperatures, iceberg scour, sea ice melt, ocean acidification, fishing pressures, pollution and non-indigenous species. Some of the most vulnerable areas include the West Antarctic Peninsula, which is experiencing rapid regional warming and increased iceberg-scouring, subantarctic islands and tourist destinations where human activities and environmental conditions increase the potential for the establishment of non-indigenous species and active fishing areas around South Georgia, Heard and MacDonald Islands. Vulnerable species include those in areas of regional warming with low thermal tolerance, calcifying species susceptible to increasing ocean acidity as well as slow-growing habitat-forming species that can be damaged by fishing gears e.g., sponges, bryozoan, and coral species. Management regimes can protect seafloor habitats and key species from fishing activities; some areas will need more protection than others, accounting for specific traits that make species vulnerable, slow growing and long-lived species, restricted locations with optimum physiological conditions and available food, and restricted distributions of rare species. Ecosystem-based management practices and long-term, highly protected areas may be the most effective tools in the preservation of vulnerable seafloor habitats. Here, we focus on outlining seafloor responses to drivers of change observed to date and projections for the future. We discuss the need for action to preserve seafloor habitats under climate change, fishing pressures and other anthropogenic impacts.

Breaking All the Rules: The First Recorded Hard Substrate Sessile Benthic Community Far Beneath an Antarctic Ice Shelf - Huw J. Griffiths; Paul Anker; Katrin Linse; Jamie Maxwell; Alexandra L. Post; Craig Stevens; Slawek Tulaczyk; James A. Smith (Frontiers in Marine Science, 2021)
The seafloor beneath floating ice shelves accounts roughly a third of the Antarctic’s 5 million km 2 of continental shelf. Prior to this study, our knowledge of these habitats and the life they support was restricted to what has been observed from eight boreholes drilled for geological and glaciological studies. The established theory of sub-ice shelf biogeography is that both functional and taxonomic diversities decrease along a nutrient gradient with distance from the ice shelf front, resulting in a depauperate fauna, dominated by mobile scavengers and predators toward the grounding line. Mobile macro-benthic life and mega-benthic life have been observed as far as 700 km under an ice shelf. New observations from two boreholes in the Filchner-Ronne Ice Shelf challenge the idea that sessile organisms reduce in prevalence the further under the ice you go. The discovery of an established community consisting of only sessile, probably filter feeding, organisms (sponges and other taxa) on a boulder 260 km from the ice front raises significant questions, especially when the local currents suggest that this community is somewhere between 625 km and 1500 km in the direction of water flow from the nearest region of photosynthesis. This new evidence requires us to rethink our ideas with regard to the diversity of community types found under ice shelves, the key factors which control their distribution and their vulnerability to environmental change and ice shelf collapse.

NEOTROPICAL ALIEN MAMMALS: a data set of occurrence and abundance of alien mammals in the Neotropics - Clarissa Alves da Rosa; Bruno R. Ribeiro; Vanesa Bejarano; Fernando Henrique Puertas; Adriana Bocchiglieri; Adriana Loeser dos Santos Barbosa; Adriano Garcia Chiarello; Adriano Pereira Paglia; Adriele Aparecida Pereira; Adryelle Francisca de Souza Moreira; Agnis Cristiane de Souza; Aiesca Pellegrin; et al. (Ecology, 2020)
Biological invasion is one of the main threats to native biodiversity. For a species to become invasive, it must be voluntarily or involuntarily introduced by humans into a nonnative habitat. Mammals were among first taxa to be introduced worldwide for game, meat, and labor, yet the number of species introduced in the Neotropics remains unknown. In this data set, we make available occurrence and abundance data on mammal species that (1) transposed a geographical barrier and (2) were voluntarily or involuntarily introduced by humans into the Neotropics. Our data set is composed of 73,738 historical and current georeferenced records on alien mammal species of which around 96% correspond to occurrence data on 77 species belonging to eight orders and 26 families. Data cover 26 continental countries in the Neotropics, ranging from Mexico and its frontier regions (southern Florida and coastal‐central Florida in the southeast United States) to Argentina, Paraguay, Chile, and Uruguay, and the 13 countries of Caribbean islands. Our data set also includes neotropical species (e.g., Callithrix sp., Myocastor coypus , Nasua nasua) considered alien in particular areas of Neotropics. The most numerous species in terms of records are from Bos sp. ( n = 37,782), Sus scrofa ( n = 6,730), and Canis familiaris ( n = 10,084); 17 species were represented by only one record (e.g., S yncerus caffer, Cervus timorensis, Cervus unicolor, Canis latrans ). Primates have the highest number of species in the data set ( n = 20 species), partly because of uncertainties regarding taxonomic identification of the genera Callithrix, which includes the species Callithrix aurita, Callithrix flaviceps, Callithrix geoffroyi, Callithrix jacchus, Callithrix kuhlii, Callithrix penicillata , and their hybrids. This unique data set will be a valuable source of information on invasion risk assessments, biodiversity redistribution and conservation‐related research. There are no copyright restrictions. Please cite this data paper when using the data in publications. We also request that researchers and teachers inform us on how they are using the data.